Evaluating the impacts of visitation on vegetation associated with waterfalls in Tijuca National Park (RJ, Brazil) - Menéndez, Inés Gómez; Zaú, André Scarambone; Sartori, Richieri Antônio (Revista Brasileira de Ecoturismo (RBEcotur), 2018)
The Tijuca National Park is considered to be the world’s second largest urban forest, and was contemplated by the first project project for the recuperation of degraded habitats in Brazil. As it is located in the center of Brazil’s second-largest city, Rio de Janeiro, Tijuca is also a popular attraction for both tourists and residents, and includes features such as scenic lookouts, waterfalls, and trails. In 2014, a research program was initiated to evaluate anthropogenic impacts on the diverse biological communities found in the vicinity of the waterfalls in which visitors bathe. In this context, the present study evaluated the impacts on the vegetation, with the aim of providing park administrators with guidelines for the regulation and management of these leisure activities. The study focused on the waterfalls located upstream from the Baronesa bridge, and the impacts on the local shrubby/arboreal-regenerative stratum. Data were collected in 10 plots of 10 m x 2.5 m located in the vicinity of the river, for comparison with an additional 10 plots located at a distance of 30 m from the river, in areas that suffer less direct impact from visitation. A number of parameters were compared between the sets of plots, including indices of diversity and evenness, mean height, basal area, density, and the presence of tillers, and exotic and endangered species, the edaphic conditions, the proportion of exposed soil, and the slope. The data were analyzed using both univariate (Student’s t, Mann-Whitney’s U) and multivariate (NMDS, Cluster Analysis, ANOSIM and NPMANOVA) procedures. The results indicated that the composition of the vegetation varied significantly between environments, with a lower diversity and greater structural homogeneity being found closer to the river. This indicates the simplification of the plant community in this environment, which was interpreted as evidence of degradation caused directly by visitors. The exposure of the soil and the number of individuals with tillers – that could be a result of the systematic breaking of saplings – were significantly greater in the plots adjacent to the river. This indicated that visitors to the waterfalls had a direct impact on the riparian vegetation. Avaliação de impactos da visitação na vegetação associada a cachoeiras no Parque Nacional da Tijuca (RJ) RESUMO O Parque da Tijuca é considerado a segunda maior floresta urbana do mundo, na qual ocorreram os primeiros projetos de recuperação de áreas degradadas do Brasil. Por conta de estar localizada no centro da segunda maior cidade brasileira, o Rio de Janeiro, é também uma atração para turistas e residentes, com muitas cachoeiras e trilhas. Em 2014 foi iniciado no Parque um conjunto de pesquisas para avaliar impactos antrópicos sobre diversas comunidades biológicas em uma área de quedas d’água, utilizadas para banho pelos visitantes, apesar das restrições descritas no Plano de Manejo. O objetivo deste trabalho foi avaliar e auxiliar na decisão da administração do Parque de manejar essa atividade nas cachoeiras situadas à montante da Ponte da Baronesa, entre elas a Cascata da Gruta, a Cachoeira da Gabriela e a Cachoeira da Diamantina, avaliando impactos sobre o estrato arbustivo/arbóreo-regenerante. Alocamos 10 parcelas de 10x2,5m no entorno do rio: a priori com influência antrópica direta; e 10 parcelas distantes 30m dessas: em tese trechos menos sujeitos ao impacto direto da visitação. Foram calculados indicadores de diversidade (riqueza observada, esperada e equabilidade), fitossociologia (Índice de Valor de Importância, considerando densidade, dominância e frequência), estrutura da vegetação (altura média, área basal, densidade de indivíduos, proporção de indivíduos com múltiplos perfilhos, proporção de indivíduos de espécies exóticas, proporção de indivíduos de espécies ameaçadas) e condições edáficas (proporção de solo exposto e declividade). Foram realizadas comparações estatísticas univariadas através dos testes de "t de Student" e Mann Whitney, e multivariadas (NMDS, Análise de Agrupamento, ANOSIM e NPMANOVA). Os resultados apontaram composição florística distinta nos dois ambientes, com menor diversidade e maior homogeneidade estrutural na vegetação imediatamente às margens do rio. Levantamos a hipótese de simplificação da comunidade vegetal neste contexto, sendo esse fato interpretado como um indicativo de degradação antrópica. A exposição do solo e a proporção de indivíduos perfilhados (possível resultado de quebra sistemática de galhos e arvoretas), significativamente maiores no entorno do rio, foram apontados como impactos associados ao trânsito de visitantes. PALAVRAS-CHAVE: Gestão da Visitação; Impacto Antrópico; Unidades de Conservação.